The power of connection: Exploring the role of identification in the emotional relationship between humans and robots in the hospitality industry - Rodrigues, A. F.; Loureiro, S. M. C.; Bilro, R. G. (16th Annual Conference of the EuroMed Academy of Business. Business Transformation in Uncertain Global Environments, 2023)
Identifying market trends is critical for companies to remain competitive, and using technologies such as Artificial Intelligence and Robotics is transforming all business industries and society, impacting experiences and relationships among people. The hospitality industry, which traditionally relies on Human-Human Interactions, is also undergoing technological transformation, with AI and social robots presenting significant potential for growth and new ways of interacting. However, technologies understanding how robots can improve hospitality services and increase customer satisfaction while maintaining a hospitable environment is crucial.